Buffer or amplifier? Longitudinal effects of social support for functional autonomy/dependence on older-adults’ chronic-pain experiences - Matos, M. (2017)
Objective: This longitudinal study aimed to investigate (a) the moderating role of formal social support for functional autonomy versus dependence on the relationship between pain intensity and pain-related disability among older adults with chronic pain and (b) the mediating role of pain-related self-efficacy and pain-related fear in this moderation. Method: One hundred and seventy older adults (Mage = 78.0; SD = 8.7) with chronic musculoskeletal pain participated in a 3-month prospective study, with 3 measurement moments. Participants filled out the Formal Social Support for Autonomy and Dependence in Pain Inventory, the Portuguese versions of the Brief Pain Inventory, the Pain Self-Efficacy Questionnaire, and the Tampa Scale of Kinesiophobia. Results: Using structural equation modeling, it was found that perceived promotion of autonomy, at Time 1, moderated the relationship between pain intensity (T1) and pain-related disability (T2); this moderation was fully mediated by pain-related self-efficacy (T2). Perceived promotion of dependence was not a significant moderator. Conclusions: These findings highlight the importance of social support for functional autonomy in buffering the impact of pain intensity on older adults’ pain-related disability. Also, they clarify the role of pain-related self-efficacy in this effect. Implications for the development of intervention programs, with formal caregivers, to reduce the impact of chronic pain on older adults’ healthy ageing process, are discussed.